2015
DOI: 10.1590/s1517-838246120131195
|View full text |Cite
|
Sign up to set email alerts
|

Torque teno virus among dialysis and renal-transplant patients

Abstract: Patients who undergo dialysis treatment or a renal transplant have a high risk of blood-borne viral infections, including the Torque teno virus (TTV). This study identified the presence of TTV and its genome groups in blood samples from 118 patients in dialysis and 50 renal-transplant recipients. The research was conducted in a hospital in the city of Maringá, state of Paraná. The viral DNA, obtained from whole blood, was identified by using two nested Polymerase Chain Reactions (PCR). The frequencies of TTV w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
2
13
1
2
Order By: Relevance
“…various surgical procedures) represent potential gateways for anelloviral particles access into the blood stream; whilst there are no studies to support this theory, in our study significantly higher rates of anelloviral DNA (Table 2 ) were found in subjects that underwent these procedures. The incidence of TTV DNA in patients undergoing haemodialysis reported by this study (90.6%), all part of the T2DM group, was higher compared to dialyzed patients from Brazil (17–36%) [ 23 ] and France (54%) [ 24 ]; however the discrepancy can be explained also by the different protocols used for molecular detection of viral DNA. For the patients undergoing haemodialysis (T2DM with chronic renal failure) the significantly higher prevalence of anelloviral DNA can be partially explained by this medical procedure.…”
Section: Discussioncontrasting
confidence: 57%
“…various surgical procedures) represent potential gateways for anelloviral particles access into the blood stream; whilst there are no studies to support this theory, in our study significantly higher rates of anelloviral DNA (Table 2 ) were found in subjects that underwent these procedures. The incidence of TTV DNA in patients undergoing haemodialysis reported by this study (90.6%), all part of the T2DM group, was higher compared to dialyzed patients from Brazil (17–36%) [ 23 ] and France (54%) [ 24 ]; however the discrepancy can be explained also by the different protocols used for molecular detection of viral DNA. For the patients undergoing haemodialysis (T2DM with chronic renal failure) the significantly higher prevalence of anelloviral DNA can be partially explained by this medical procedure.…”
Section: Discussioncontrasting
confidence: 57%
“…This may have been a chance finding, given the small numbers involved; however, it is consistent with a Brazilian study which also found a higher prevalence in transplant compared with dialysis patients. 23 Another potential explanation is that TTV is present in >90% of all people, but it may be at viral loads below the level of detection of our assay (500 copies/mL) and hence not be detectable until after immunosuppression. Finally, the prevalence may be truly higher in transplant patients due to more acquisition, but this appears unlikely; for example, previous blood transfusion (one potential mechanism of acquisition) was reported in a similar proportion of dialysis patients (52%) and transplant patients (60%).…”
Section: Implications and Comparison With The Literaturementioning
confidence: 95%
“…Имеется ряд работ, посвященных анализу обнаружения TTV у пациентов, проходящих лечение гемодиализом [22,76,78,81]. Обобщая данные, представленные в этих работах, можно сделать вывод, что частота обнаружения ДНК TTV в крови пациентов, подвергающихся процедуре гемодиализа, статистически выше, чем у доноров крови.…”
Section: пути передачиunclassified
“…Ряд работ подтверждает, что частота обнаружения ДНК TTV у пациентов, подвергшихся трансплантации органов, статистически выше, нежели до операции или чем у доноров крови [81][82][83]87]. По данным Y. Kanda и соавт., из 25 реципиентов костного мозга 60 % становились инфицированными TTV через 6-12 недель после трансплантации [93].…”
Section: пути передачиunclassified